Training and physiological characteristics of American and Japanese female track and field athletes - Tsukahara, Y.; Mason, R. A.; Macznik, A. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Intensive training without appropriate recovery can predispose athletes to injury. Balancing these two facets - training and recovery - is crucial for keeping athletes at their highest possible performance level while lowering their risk of training-related injury. Cultural differences may also affect athletes` training and daily routines, but research investigating the effects of cultural background on female track and field athletes is lacking. METHODS: In total, 49 Japanese and 28 American track and field athletes competing at the national level were included in this study. Their body composition was evaluated and eating attitudes test (EAT-26) and a survey regarding training schedules, recovery practices, and performance levels were conducted. RESULTS: Compared with the Japanese athletes, the American athletes had significantly higher height, weight, and Body Mass Index measurements, although their performance levels did not differ. Japanese athletes trained for significantly longer hours both on school days and non-school days and spent significantly fewer days per week on weight training. The Japanese athletes slept, on average, for 1 hour less per day than the American athletes, and their EAT-26 scores were significantly higher than those of the American athletes (both P<0.01). The number of days off per week was positively correlated with performance, but training hours on school days and fat mass percentage were negatively correlated with performance (P<0.05). Further, days off per week and nationality were correlated with EAT-26 scores (both P<0.05). CONCLUSIONS: The American and Japanese athletes performed similarly, but the Japanese athletes were achieving their performance level with less sleep, longer training hours, and a higher risk of developing an eating disorder.